(3efY GdehGfY Yf LeY GdLhGeYs - (3YHO GdhgGH Hf Ydj Hf YHO GdcGaj GdSHcj, CHh fUQ , JGL GdOjf , J (B771 (3g` s ((3CMeO Hf CHj HcQ Hf eci GdMfHdi s)
(3ChdgG (B:s
(3GdeSDhd ef EMSGf SjOfG Cf jhVM dfG eG CTcd YdjfG hOb ageg ef CdaGXg GdTQjag ai cJGHg LeY GdLhGeY s
(3BNQgG (B:s
(3hgj eSCdI NdGajI ebQQI ai TQM GdeNJUQ adjfXQ hGddg JYGdi CYde JeJ GdGLhHI s
(3HChdg eWGdYGJs
(3cJHJ GdfSNI HNW bdjd GdfbWs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3CUhd Gdabgs